Perspectives of learning science effectively: comparison between Western Australian teachers and Malaysian teachers - Sulaiman, Tajularipin; Baki, Roselan; Abdul Rahim, Suzieleez Syrene (Universiti Putra Malaysia Press, 2011)

(untitled)
Malaysia hopes to be a developed country which is driven by the industrial and agricultural sectors by the year 2020. This aspiration is guided by Vision 2020 and in order to achieve this, the manpower of the country must be developed and furnished with strong technological, mathematical, and science backgrounds as early as the primary level. It is important to note that effective learning influences the attitude of the students towards science, and if Malaysia is to develop in accordance with Vision 2020, this issue must be addressed. In developed countries like Australia, the learning of science is developed humanistically to attract students to science. The learning of science in Australia involves materials, environments, and activities which encourage students to actively participate in the class. Therefore, it is important to investigate teachers’ perspectives towards students’ learning as teachers are facilitators of learning. This paper discusses the findings of a qualitative study that was carried out to compare the perspectives of primary science teachers from Malaysia and from Western Australia, with the focus on five research questions. The first question is “what are the teachers’ perspectives of learning science?”, whereas the second, third and fourth are, “what are the teachers’ perspectives of effective teaching methods, the importance of teaching aids and implementing science process skills in the learning of science?” and the fifth question is, “how to assess the progress of the students in learning science?” The participants of the study were twelve primary science teachers from Western Australia and from Malaysia, respectively. The data collection approaches employed included open-ended questions, non-participant observation techniques, and document collection. The findings indicated that there are four types of teachers’ perspectives of learning science, three perspectives of the implementation of science process skills in learning science, and five methods in assessing students’ progress in learning science.